The Effectiveness of Using Motion Graphics in Acquiring English Vocabulary among Second-Grade Intermediate Students - Khawlah Abdulaaziz M. Al-Turki; Latifah Abdullah K Alharbi (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية)
This study aimed to determine the effectiveness of using motion graphics in teaching a unit of the English language course for the second intermediate grade in acquiring vocabulary among second-grade intermediate students. The study used the English vocabulary test as an instrument to collect data and measure the effectiveness of the independent variable of the study. The test was performed twice, before and after the treatment was applied to the groups. The study used a quasi-experimental design. The study population was selected from one of the female intermediate schools in Unayzah Governorate in Al Qassim region. The study sample consisted of (54) second-grade intermediate Female students aged between (14-15) years, assigned randomly as experimental and control groups. The sample was divided into two groups, (27) students in each. The study concluded that there are statistically significant differences between the average scores of the experimental group students and the scores of the control group students in the results of the vocabulary acquisition post-test in favor of the experimental group. The study recommended using a variety of instructional strategies to meet the diverse needs and preferences of learners as well as ensure that the instructional materials and resources are accessible to all students, including those with diverse learning needs and backgrounds.